Impact of the positive electron–hole exchange interaction constant on the binding energy of neutral donor bound excitons in AlN. (3rd August 2021) - Ishii, Ryota; Yoshikawa, Akira; Kobayashi, Hirotsugu; Funato, Mitsuru; Kawakami, Yoichi
Abstract: Low-temperature photoluminescence spectroscopy is performed for unintentionally doped and silicon-doped aluminum nitride (AlN) films grown on AlN substrates. Considering the positive electron–hole exchange interaction constant substantially changes the neutral silicon-donor bound exciton binding energy from 28.5 to 15.3 meV. The silicon-donor binding energy is also experimentally deduced as 64.8 meV from a two-electron transition, which is justified by a theoretical calculation considering the crystal anisotropy and electron–phonon coupling. The estimated binding energies are discussed with a previous theoretical result within the effective mass approximation and the experimentally known binding energy of elementary four-particle (three-particle) systems.